A Fully-Immersive Virtual Reality Setup to Study Gait Modulation - Palmisano, Chiara; Kullmann, Peter; Hanafi, Ibrahem; Verrecchia, Marta; Latoschik, Marc Erich; Canessa, Andrea; Fischbach, Martin; Isaias, Ioannis Ugo (Frontiers in Human Neuroscience, 2022)
Objective. Gait adaptation to environmental challenges is fundamental for independent and safe community ambulation. The possibility of precisely studying gait modulation using standardized protocols of gait analysis closely resembling everyday life scenarios is still an unmet need. Methods. We have developed a fully-immersive virtual reality (VR) environment where the subject has to adjust their walking pattern to avoid collision with a virtual agent (VA) crossing their gait trajectory. We collected kinematic data of 12 healthy young subjects walking in real world (RW) and in the VR environment, both with (VR/A+) and without (VR/A-) the VA perturbation. The VR environment closely resembled the RW scenario of the gait laboratory. To ensure standardization of the obstacle presentation, the starting time, speed, and trajectory of the VA were defined using the kinematics of the participant as detected online during each walking trial. Results. We did not observe kinematic differences between walking in RW and VR/A-, suggesting that our VR environment per se might not induce significant changes in the locomotor pattern. When facing the VA, all subjects consistently reduced stride length and velocity, while increasing stride duration. Trunk inclination and mediolateral trajectory deviation also facilitated avoidance of the obstacle. Conclusions. This proof-of-concept study shows that our VR/A+ paradigm effectively induced a timely gait modulation in a standardized immersive, and realistic scenario. This protocol could be a powerful research tool to study gait modulation and its derangements in relation to aging and clinical conditions.